ANALYSIS OF FACTORS AFFECTING THE COMPETITIVENESS OF PORTS - Blohins, Viktors (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Globalization and the growth of world trade force ports to change accordingly to changing market conditions. Ship sizes grow rapidly, so ports should deepen the harbour, modify port equipment and train personnel. In other worlds – ports have to be ready to react. The challenge of finding the vectors of development in those changing conditions is a crucial fact. In the paper, the author analyses the extent of the research work done in the sphere of competitiveness of ports and deals with the main factors influencing the position of ports in the world market. Therefore, the purpose of the work is to highlight the major factors affecting the port competitiveness. The main research method is the theoretical research. The analysis is based on the research carried out by scientists in the field of competitiveness of ports. As a result, three main factors were identified and described. The most important factor affecting the competitiveness of the port is the development of port hinterlands. Development initiatives of these territories and the relations between them should be laid down in each port’s development plan. Remaining factors are regular shipping lines existence and value added services in ports. Other factors that influence the overall port position on the market are also being reviewed.